PENGARUH KETERLIBATAN PELANGGAN, SIKAP PEMBELIAN, DAN PERSEPSI KEMUDAHAN PENGGUNAAN APLIKASI SOCIOLLA TERHADAP NIAT BELI PRODUK SKINCARE MELALUI PEMASARAN VIRAL SEBAGAI VARIABEL INTERVENING - Khalisha Rizky Bani Rachmad; Yudi Sutarso (Program Magister Manajemen STIE Widya Wiwaha Yogyakarta, 2023)
The viral marketing phenomenon occurred in cyberspace drives many changes in the marketing. In the past several years, there was a lot of viral news spreading in the society. In the skincare sector, industry attracts many fans through various ways, included viral message dissemination. Sociolla became the one of platform that produced feasibility for users to earn huge benefit from viral messages in the form of reviews written by other users. This study aimed to measure the effect of viral marketing, perceived ease of use of applications, purchase attitudes, and customer involvement in skincare products on the sociolla platform on people purchase intentions. This study used quantitative research with descriptive analysis techniques using WARP-PLS. The sampling technique used was non-probability sampling with a purposive sampling technique. The sample of this study was 111 sociolla users in Surabaya, Sidoarjo, and surrounding areas. The results of this study indicate that viral marketing on perceptions of the ease of use of applications and purchase attitudes do not affect purchase intentions. Besides, the perceived ease of use of the application affects purchase attitudes and purchase attitudes affect purchase intentions. Moreover, customer engagement affects purchase intention and viral marketing.